ROLE OF MATHEMATICS IN ANALYSTS SPECIALISTS TRAINING: PROBLEMS AND PRACTICE - Mihail V. Karmanov; Valeriy A. Nikishkin (Открытое образование (Москва), 2016)
The 21st century is marked by the need of analytical activity as the means for efficient management solutions. Notwithstanding, modern system of training of the qualified analysts is impossible without acquiring knowledge in Mathematics. As a result, it seems to be interesting from the science and practice approach to study with a minute care the role of the mathematical knowledge in training analytical ideology, especially in the context of current problems and experience in their solutions.